2018
DOI: 10.5582/bst.2018.01105
|View full text |Cite
|
Sign up to set email alerts
|

The proangiogenic role of polymorphonuclear myeloid-derived suppressor cells in mice infected with <i>Echinococcus granulosus </i>

Abstract: The aim of this study was to first evaluate the proangiogenic activity of polymorphonuclear myeloid-derived suppressor cells (PMN-MDSC) in mice infected with Echinococcus granulosus. PMN-MDSCs derived from experimentally infected mice were collected and cultured in vitro, and their effect on angiogenesis was investigated using a human umbilical vein endothelial cell (HUVEC) tube-formation assay stimulated with the supernatant by microscope and the Angiogenesis module of the software NIH Image J. In addition, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…A study found that MDSCs may interact with lysosomal acid lipase to cause dysfunction of ECs (16). Moreover, in vitro experiments have shown that the culture supernatant of PMN-MDSCs can significantly promote the tube formation of HUVECs (143). This finding indicates that PMN-MDSCs may secrete some pro-angiogenic factors.…”
Section: Myeloid-derived Suppressor Cellsmentioning
confidence: 98%
“…A study found that MDSCs may interact with lysosomal acid lipase to cause dysfunction of ECs (16). Moreover, in vitro experiments have shown that the culture supernatant of PMN-MDSCs can significantly promote the tube formation of HUVECs (143). This finding indicates that PMN-MDSCs may secrete some pro-angiogenic factors.…”
Section: Myeloid-derived Suppressor Cellsmentioning
confidence: 98%
“…The persistent infection of E. granulosus can span many years due to its evasion strategies. The interaction network between immune and immunosuppressive cells can increase the immune microenvironment complexity at the lesion site during infection ( 6 , 7 ). Angiogenesis contributes to hydatid cyst growth, and endothelial cells are key in tissue angiogenesis ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…Each group has a different biological function and different mechanism involved in its mediation function [ 15 , 16 ]. In addition to tumors, recent studies have shown that some parasites (such as trypanosoma, nematodes and echinococcus) infection can induce the production of MDSCs, and MDSCs plays an important role in the occurrence and development of these parasitic diseases [ 21 23 ]. Our previous study found a large number of MDSCs aggregations in the spleen and lymph nodes of mice infected with S .…”
Section: Introductionmentioning
confidence: 99%